Aleochara (Coprochara) bimaculata Gravenhorst 1802 ... - Klimaszewski, Jan; Chandler, Donald S.; Davies, Anthony; Bourdon, Caroline (Zenodo, 2023)
1. Aleochara (Coprochara) bimaculata Gravenhorst (Illustrations in Klimaszewski 1984, Klimaszewski et al. 2018), Table 1 References. Gravenhorst 1802; Klimaszewski 1984; Klimaszewski et al. 2018, 2021. Distribution. Nearctic; widely distributed in Americas, reported from Arctic/Subarctic (A/S) (Klimaszewski et al. 2021). Canada: AB, BC, LB, MB, NB, NF, NS, NT, ON, QC, SK. USA: AL, AZ, CA, CO, DC, FL, GA, ID, IL, IN, IA, KS, KY, LA, MA, MD, ME, MI, MN, MO, MT, NC, NE, ND, NH, NJ, NM, NV, NY, OK, OR, PA, RI, SC, SD, TN, TX, UT, VA, VT, WA, WV, WI, WY. Mexico. Colombia. Ecuador. Brazil. Chile. Argentina. Collection and Habitat data. Found in pig dung in a pasture on a farm in NH. Taken from June to October. Elsewhere recorded from diverse open and treed habitats; adults found in human feces and other animal droppings such as cow, horse, deer, dog; carcasses of dead animals such as rabbit, fish; decaying fungi, moss and leaf litter along streams, and plant debris in beaver lodges (Klimaszewski et al. 2018). ... : Published as part of Klimaszewski, Jan, Chandler, Donald S., Davies, Anthony & Bourdon, Caroline, 2023, Aleocharine rove beetles of New Hampshire, USA: new taxa and new records (Coleoptera, Staphylinidae, Aleocharinae), pp. 1-141 in Zootaxa 5364 (1) on pages 9-10, DOI: 10.11646/zootaxa.5364.1.1, http://zenodo.org/record/10145460 ...